A High Regulated Low Ripple DC Power Supply Based on LC Filter and IGBT - Ayan Mitra; Abhisek Roy (Institute of Advanced Engineering and Science, 2013)
Filaments operating at a high temperature region would require ripple free current constant power source for their heating purposes. Introduction of ripple in the power supply would result in high power loss, aberrant, unpredictable temperature rise etc. High current ripple can also extenuate the life of electrolytic capacitors used in the circuit. In this paper we propose a scheme in which we would not only use simple, low cost, easily available electronic components but also reduce the value of ripple factor to <0.1% and load regulation to 0.1%.DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.696